Permeabilitas Membran Transpor Campuran Unsur Tanah Jarang (La, Nd, Gd, Lu) Menggunakan Carrier (TBP : D2EHPA) Melalui Supported Liquid Membrane - Djabal Nur Basir (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
Methods that have been developed currently for the separation and purification of rare earth elements, REE’s are solvent extraction by through immobilization of an extracting agent in a porous polymeric membrane. This methods beside could increase the transport selectivity, also the amount of carrier was very few. This technique is known as supported liquid membrane, SLM. Research toward transport and separation of REE’s through SLM have been still relatively limited merely to single feed-binary mixture, and one type of carrier. The transport membrane permeability was obtained in a mixture of REE’s (La,Nd,Gd,Lu) using the carrier TBP : D2EHPA by SLM. In this SLM technique, supporting membrane PTFE (polytetrafluoroethylene) was soaked in a mixture of TBP carrier (tributilfosfat) as a neutral ligand and D2EHPA (acid-2- etilheksilfosfat) as anionic ligand with a particular concentration ratio in the solvent kerosene as membrane phase. HCl as receiver phase and solution mixture of REE’s as feed phase. Determination of the REE’s total concentration was carried out by UV-Vis spectrophotometry with NAS (sodium alizarin sulfonate) as the colouring agent at pH 4,75 and the solution absorbance was determinated at 534 nm as maximum wavelength. Transport patterns of REE’s on the variation of the concentration of total mixed carrier composition, pH, and concentration of the receiver phase were done for 300 minutes. The optimum conditions of transport mixture of REE’s (La, Nd, Gd, Lu) were feed phase pH 3,0; carrier TBP: D2EHPA (0,3:0,7) M; and receiver phase HCl 3,0 M. In this condition, the transport membrane permeability in mixture of REE’s was 0,1077 cm.menit-1 with the percent of transport was 95,24%.